THE REPRESENTATION OF SOCIAL ISSUES IN KITA PERGI HARI INI NOVEL BY ZIGGY ZEZSYAZEOVIENNAZABRIZKIE - Nur Hafnizar; Bima Prana Chitra; Hidayati (Hikamatzu | Journal of Multidisciplinary, 2024)
Because of the many social problems raised by the novel Kita Pergi Hari Ini, as well as the phenomenon of social problems in society makes the main reason for the writer to choose Kita Pergi Hari Ini novel as a research topic. This study aims to reveal the types of social issues that occur in Kita Pergi Hari Ini novel by Ziggy Zezsyazeoviennazabrizkie and to explain the author's worldview towards social issues in  Kita Pergi Hari Ini novel. This study uses Genetic structuralism theory with the concept of the author’s worldview by Lucien Goldmann. The writer uses qualitative research method and uses Phenomenological approach. The data source of this study is from dialogues and monologues in the novel, data is collected using a reading and note-taking technique. After doing this research, the writer found the results of this research are: 1) There are 3 social issues contained in this novel, poverty, crime, and population problems, 2) the author uses children’s point of view, dark words, her experiences, word games in the story to express her views on social issues that occur in society, then reflected in fantasy stories.